Inward currents induced by ischemia in rat spinal cord dorsal horn neurons - Gu Jianguo G; Tao Yuan-Xiang; Chen Meng (SAGE Publishing, 2007)
Abstract Hypoxia and ischemia occur in the spinal cord when blood vessels of the spinal cord are compressed under pathological conditions such as spinal stenosis, tumors, and traumatic spinal injury. Here by using spinal cord slice preparations and patch-clamp recordings we investigated the influence of an ischemia-simulating medium on dorsal horn neurons in deep lamina, a region that plays a significant role in sensory hypersensitivity and pathological pain. We found that the ischemia-simulating medium induced large inward currents in dorsal horn neurons recorded. The onset of the ischemia-induced inward currents was age-dependent, being onset earlier in older animals. Increases of sensory input by the stimulation of afferent fibers with electrical impulses or by capsaicin significantly speeded up the onset of the ischemia-induced inward currents. The ischemia-induced inward currents were abolished by the glutamate receptor antagonists CNQX (20 μM) and APV (50 μM). The ischemia-induced inward currents were also substantially inhibited by the glutamate transporter inhibitor TBOA (100 μM). Our results suggest that ischemia caused reversal operation of glutamate transporters, leading to the release of glutamate via glutamate transporters and the subsequent activation of glutamate receptors in the spinal dorsal horn neurons.